Pengaruh Kompetensi Auditor, Pengalaman Auditor, Dan Fee Audit Terhadap Kualitas Laporan Audit Pada Kantor Akuntan Publik Di Kota Surakarta - Tursina andrianingsih; Maya Widyana Dewi; LMS Kristiyanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This article examines how auditor competence, auditor experience, and audit fees relate to the quality of audit reports produced by public accounting firms in Surakarta City. Audit report quality is treated as a central indicator of professional audit performance because the audit report communicates the reliability of financial statements to external users and supports economic decision-making. The research applied a quantitative design using primary data obtained from structured questionnaires administered to auditors employed by public accounting firms in Surakarta City. From 72 questionnaires distributed, 50 responses were returned and considered suitable for analysis. The data were evaluated through instrument testing, classical assumption testing, multiple linear regression, the F-test, the t-test, and the coefficient of determination. The partial results show that auditor competence does not have a significant effect on audit report quality, auditor experience has a significant effect, and audit fees do not have a significant effect. Simultaneously, however, auditor competence, auditor experience, and audit fees jointly influence audit report quality. The adjusted R-square value of 0.247 demonstrates that the three predictors account for 24.7% of the variation in audit report quality, whereas 75.3% is attributable to factors beyond the model. The evidence emphasizes the practical importance of assigning experienced auditors, strengthening engagement supervision, and maintaining effective quality-control procedures within public accounting firms. Keywords : auditor competence; auditor experience; audit fees; audit report quality; public accounting firms.